2020
DOI: 10.1371/journal.ppat.1008652
|View full text |Cite
|
Sign up to set email alerts
|

A secreted LysM effector protects fungal hyphae through chitin-dependent homodimer polymerization

Abstract: Plants trigger immune responses upon recognition of fungal cell wall chitin, followed by the release of various antimicrobials, including chitinase enzymes that hydrolyze chitin. In turn, many fungal pathogens secrete LysM effectors that prevent chitin recognition by the host through scavenging of chitin oligomers. We previously showed that intrachain LysM dimerization of the Cladosporium fulvum effector Ecp6 confers an ultrahigh-affinity binding groove that competitively sequesters chitin oligomers from host … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 52 publications
3
40
1
Order By: Relevance
“…Then we applied the pipeline to predict binding of the DP4 oligomer to OsCEBiP, the rice chitin receptor, and its co‐receptor OsCERK1, and we found that the pipeline predicted OsCEBiP binding to the DP4 oligomer, but not to OsCERK1 (Figure S2), as described previously (Liu et al ., 2016). Next, we applied the pipeline to the fungal effectors Cf Avr4F and Mg1LysM, which bind to the DP6 chitin oligomer (Hurlburt et al ., 2018; Sánchez‐Vallet et al ., 2020), and we found that the model positively predicted their binding to the DP6 oligomer (Figure S2), further confirming the robustness of the pipeline developed (Figure 3).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Then we applied the pipeline to predict binding of the DP4 oligomer to OsCEBiP, the rice chitin receptor, and its co‐receptor OsCERK1, and we found that the pipeline predicted OsCEBiP binding to the DP4 oligomer, but not to OsCERK1 (Figure S2), as described previously (Liu et al ., 2016). Next, we applied the pipeline to the fungal effectors Cf Avr4F and Mg1LysM, which bind to the DP6 chitin oligomer (Hurlburt et al ., 2018; Sánchez‐Vallet et al ., 2020), and we found that the model positively predicted their binding to the DP6 oligomer (Figure S2), further confirming the robustness of the pipeline developed (Figure 3).…”
Section: Resultssupporting
confidence: 76%
“…Our in silico computational minimization procedure further supports these recent data. Similarly, the computational calculations performed here with rice OsCEBiP and OsCERK1 and some fungal effectors ( Cf Avr4 and Mg1LysM) that bind chitin (Figure S2) also confirmed published data (Liu et al ., 2016; Hurlburt et al ., 2018; Sánchez‐Vallet et al ., 2020) and supported the robustness of glycoligand/PRR binding predictions by the in silico computational minimization procedure described here. Remarkably, this technical advance might also allow the identification of key PRR residues involved in binding and stabilization of glycan structures, as shown here with the in silico validation of the relevance of Q109 and I141 from CERK1 in 1,4‐β‐ d ‐(GlcNAc) 6 binding (Figure S6).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Chitin, an unbranched homopolymer of 1, 4-β linked N-acetyl-D-glucosamine (GlcNAc), is the second most abundant polysaccharide on earth and is the major component of fungal cell walls. As a major pathogen-associated molecular pattern (PAMP) in rice, chitin is recognized by the pattern recognition receptor (PRR) CEBiP and coreceptor OsCERK1 on plant cell membrane, and thus initiating immune responses (Gong et al 2020 ; Sanchez-Vallet et al 2020 ; Shimizu et al 2010 ). For successful infection, fungal pathogens have evolved to secrete certain effector proteins to interfere with PAMP recognition by PRRs.…”
Section: Pathogenicity Factors In R Solanimentioning
confidence: 99%
“…The selection of an effector to identify the corresponding effector target requires insights into the process a given effector is involved in. For example, effectors containing lysin motifs (LysMs), referred to as LysM effectors, were shown to perturb chitin-induced immunity by binding chitin through intermolecular LysM dimerization which protects fungal cell walls against host chitinases (Kombrink and Thomma, 2013;Sánchez-Vallet et al, 2020;Tian et al, 2020). Another example is the V. dahliae effector Avirulence on Ve1 tomato (Ave1).…”
Section: Know the Enemy's Strategy To Win -Exploring Effector Targetsmentioning
confidence: 99%